2023
DOI: 10.1039/d3me00082f
|View full text |Cite
|
Sign up to set email alerts
|

Graphene in rubber formulations: a comprehensive review and performance optimization insights

Y. L. Leong,
H. N. Lim,
I. Ibrahim

Abstract: Graphene is widely incorporated into rubber matrices to enhance mechanical, electrical, and thermal properties in nanocomposites. However, its hydrophobicity and lack of functionalities cause agglomeration, impacting nanocomposite properties. Intense agitation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 226 publications
(559 reference statements)
0
5
0
Order By: Relevance
“…For the linear viscoelastic region, the energy loss factor W can be determined as: 𝑊 = 𝜋 𝑡𝑎𝑛δ 𝜋 𝑡𝑎𝑛δ + 1 (15) where tanδ is the dissipation factor. The volume of the constrained region Cv can be determined from the dynamic viscoelastic region by using the following equation: It can be observed that the height of the tanδ peak for compound 2 is comparatively lower than for the other compounds.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 99%
See 2 more Smart Citations
“…For the linear viscoelastic region, the energy loss factor W can be determined as: 𝑊 = 𝜋 𝑡𝑎𝑛δ 𝜋 𝑡𝑎𝑛δ + 1 (15) where tanδ is the dissipation factor. The volume of the constrained region Cv can be determined from the dynamic viscoelastic region by using the following equation: It can be observed that the height of the tanδ peak for compound 2 is comparatively lower than for the other compounds.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 99%
“…Graphene is highly conductive compared to carbon black, which means that it can reach percolation at lower concentrations, thereby being beneficial for applications requiring static charge dissipation and temperature management [13,14]. Due to its having much stronger mechanical properties, graphene can impart improved mechanical properties to the rubber formulation, especially regarding tensile strength and tear strength [15,16]. The flexibility of rubber formulations with graphene is higher than in those with carbon black [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response surface method is cost-effective and reliable for optimizing certain processes. This method decreases the number of required tests [24]. The Box Behnken test assessed the parameters affecting the response rate.…”
Section: Design Expertmentioning
confidence: 99%
“…In the above articles, the tests were limited due to the long analysis time, large number of test steps, and high cost, and only 2 to 4 effective factors were studied. Still, in this article, all effective parameters in the synthesis of graphene are discussed and studied without limitations [23,24]. 3.…”
Section: Design Expertmentioning
confidence: 99%